PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN KESEHATAN SEBELUM DAN SETELAH PEMEKARAN KOTA TANGERANG SELATAN - Shabrina Adlina Purnamasari; Fitriyah .; Budi Setiyono (Journal of Politic and Government Studies, 2015)
The segregation of the regions is an effort to improve the quality of public services with the aim of making public welfare. South Tangerang is an autonomous region of the results of Tangerang segregation. In the end of the segregation, change and development done by the South Tangerang Government to provide good health services, at least better than the services provided before the segregation of Tangerang. Public satisfaction is a way to measure the success of service implementation. The purpose of the study is to understand the public perceptionsof health services quality before and after the segregation of South Tangerang in terms of public satisfaction index. Based on the research results, it can be seen that 10 (ten) of 14 (fourteen) service elements have increased from not good before the segregation and are considered better after the segregation based on Public Satisfaction Index. Therefore, it can concluded that public perceptions give a positive response to the quality of health service.Key Words : Public Services; Segregation; Perception; Public Satisfaction Index